DNA Methylation of Interleukin-6 (IL-6) promoter in the Leukocytes is reduced in prehypertensive young adults - Wan Omar, Wan Fatein Nabeila; Mohd Shah, Azarisman Shah; Ab Rahman, Jamalludin; A.Talib, Norlelawati; Mohd. Shah, Aida Nur Sharini; Abdullah, Aszrin (2019)
Background: Prehypertension is associated with increased risk of cardiovascular disease. Chronic inflammation plays a role in the pathophysiology of essential hypertension, with epigenetic dysregulation involvement. However, its role in prehypertensive state is not known. The aim of this study was to investigate the association between DNA methylation level of IL-6 promoter in prehypertensive (PreHT) and normotensive (NT) young adults.